KONSEP PENGELOLAAN KOPERASI PESANTREN UNTUK KESEJAHTERAAN EKONOMI MASYARAKAT: TELAAH SURAH AL-HASYR AYAT 7 - Ahmad Lutfi Rijalul FIkri; Muaidy Yasin; Akhmad Jupri (ISLAMICONOMIC: Jurnal Ekonomi Islam, 2018)
Abstract. The Management of Islamic Boarding Schools Cooperative Concept for Community Economic Welfare: Study of Surah Al-Hasyr Verse: 7. Al-Qur'an with its verses becomes the economic foundation that has given the principles of life in relationships between man and his fellowmen. It contains rules and guidance for his loyalists to do good things and stay away from actions that are considered vandalism and tyranny. Therefore, Al-Qur’an which is foundation of the whole teachings of Islam is not just about the collection of rules and prohibitions, but provides assurance for the realization of economic prosperity of the community. In this article, the writer intends to reveal the clarity of the concept of pesantren cooperative management for the economic welfare of community in the perspective of sura al-Hashr verse 7. Al-Quran believes that economic welfare is not only the problem of economic distribution materially but also concerning non material and other fields. Therefore, to achieve growth and development materially and spiritually, Islamic Economics has characteristics in its growth, which is all-round, balanced, realistic, fair, responsible, sufficient and focusing on human beings in accordance with their right as khalifah on earth. These characteristics indicate that the goal of growth and economic development in Islam is the opportunity of all members of any community of race, religion and character to gain prosperity, so that everyone can experience the blessings and grace of Allah. Al-Qur'an demands all of its loyalists to carry out the whole teaching of Islam in all aspects of their life. The consequence of this concept is that economic welfare should be viewed as the embodiment of God's command to his servants. So that economic welfare is a continuous effort of mankind to do the best, both to God and fellow human beings based on the guidance of Al-Quran. Abstrak. Konsep Pengelolaan Koperasi Pesantren Untuk Kesejahteraan Ekonomi Masyarakat: Telaah Surah Al-Hasyr Ayat 7. Al-Quran dengan ayat-ayatnya menjadi landasan ekonomi yang telah memberikan prinsip-prinsip kehidupan dalam menjalin hubungan antara manusia dengan sesamanya. Di dalamnya berisi aturan dan sekaligus tuntutan agar pengikut-pengikutnya berbuat hal-hal yang baik dan menjauhi tindakan yang dianggap pengerusakan dan kedzaliman. Oleh karenanya Al-Quran yang menjadi landasan dari keseluruhan ajaran Islam tidak sekedar berisi tentang kumpulan peraturan dan larangan, tetapi memberikan jaminan untuk terwujudnya kesejahteraan ekonomi masyarakat. Pada artikel ini, penulis bermaksud mengungkap kejelasan konsep pengelolaan koperasi pesantren untuk kesejahteraan ekonomi masyarakat dalam perpektif surat al-Hasyr  ayat 7. Al-Quran memandang bahwa kesejahteraan ekonomi bukan semata-mata hanya permasalahan distribusi ekonomi secara materi semata-mata tetapi juga menyangkut unsur non materi dan bidang-bidang yang lainnya. Oleh karena itu, untuk mencapai pertumbuhan dan perkembangan secara material dan spiritual tersebut, Ekonomi Islam mempunyai karakteristik dalam pertumbuhannya, yaitu serba meliputi, berimbang, realistis, berkeadilan, tanggungjawab, mencukupi dan berfokus pada manusia sesuai dengan haknya sebagai khalifah di muka bumi. Karakteristik tersebut menunjukkan bahwa tujuan pertumbuhan dan pembangunan ekonomi dalam Islam adalah adanya kesempatan semua anggota masyarakat apapun ras, agama dan karakternya – untuk mendapatkan kesejahteraan, sehingga semua orang dapat merasakan nikmat dan karunia Allah Swt. Al-Quran menuntut para pengikutnya untuk menjalankan keseluruhan ajaran Islam dalam semua aspek kehidupannya. Konsekuensi dari konsep ini adalah kesejahteraan ekonomi harus dipandang sebagai perwujudan perintah Tuhan kepada hamba-hambanya. Sehingga kesejahteraan ekonomi  merupakan upaya terus menerus dari umat manusia untuk berbuat sebaik-baiknya, baik kepada Tuhan maupun kepada sesama manusia berdasarkan petunjuk Al-Quran